Challenges and Clinical Strategies of CAR T-Cell Therapy for Acute Lymphoblastic Leukemia: Overview and Developments - Xu, Xinjie; Huang, Shengkang; Xiao, Xinyi; Sun, Qihang; Liang, Xiaoqian; Chen, Sifei; Zhao, Zijing; Huo, Zhaochang; Tu, Sanfang; Li, Yuhua (Frontiers in Immunology, 2021)
Chimeric antigen receptor (CAR) T-cell therapy exhibits desirable and robust efficacy in patients with acute lymphoblastic leukemia (ALL). Stimulated by the revolutionized progress in FDA-approved CD19 CAR T-cells, novel agents with new CAR designs and targets are being produced in pursuit of superior performance. Although there has been abundant experience with CAR T-cell administration from former trials, such evidence is not sufficient for the bedside application of these cells as commercial products. Accessibility is considered the initial barrier to the transformation of this patient-specific product. To ensure infusion safety, profound comprehension of adverse events and proactive intervention are required. Additionally, resistance and relapse are critical issues in ALL treatment and are also intractable in CAR T-cell therapy, thus precluding its further development. Understanding the limitations through up-to-date insights and characterizing multiple strategies will be critical to organize CAR T-cell therapy flexibly for use in clinical situations. Herein, we provide an overview of the application of CAR T-cell therapy in ALL, emphasizing the main challenges and potential clinical strategies in an effort to promote the standardization process of treatment paradigms for ALL.